Systematic approaches to a successful literature review - Booth, Andrew , 1961-; Papaioannou, Diana; Sutton, Anthea (SAGE, 2012)
"Reviewing the literature is an essential part of every research project. This book takes you step-by-step through the process of approaching your literature review systematically, applying systematic principles to a wide range of literature review types. Through numerous examples, case studies and exercises, the book covers often neglected areas of literature review such as concept analysis, scoping and mapping." -- Book jacket